Role of dynamic thoracoscopy in treatment of pleural complications of bacterial destruction of the lungs in children - A. Losev; D Samofalov (Kazimierz Wielki University, 2014)
A total of 93 children with pleural complications of destructive pneumonia were randomised, and all the patients get studymethod of dynamic thoracoscopy. Evaluation of changes in lung and pleura were made. Basing to this changes-the stages of destructive process were developed. On the base of the stages patogenetical treatment was suggested. In the treatment group (n=56) method of fractional washing of pleural cavity, and the method of local antibioticotherapy was used. No complications resulted from the thoracoscopies and there was no need for further surgical intervention in any of these patients. We conclude that dynamic thoracoscopy allows for minimally invasive, yet effective treatment pleural complications of destructive pneumonia. Thoracoscopic visualization of the pleural cavity permits efficient debridement, thorough adhesiolysis, and optimal placement of drainage tubes.